Littlewood–Paley theorem on spaces Lp(t)(ℝⁿ) - Kopaliani, T.S. (Український математичний журнал, 2008)
We point out that if the Hardy–Littlewood maximal operator is bounded on the space Lp(t)(ℝ), 1 < a ≤ p(t) ≤ b < ∞, t ∈ ℝ, then the well-known characterization of the spaces Lp(ℝ), 1 < p < ∞, by the Littlewood–Paley theory extends to the space L p(t)(ℝ). We show that, for n > 1 , the Littlewood–Paley operator is bounded on Lp(t) (ℝⁿ), 1 < a ≤ p(t) ≤ b < ∞, t ∈ ℝⁿ, if and only if p(t) = const.